2014
DOI: 10.1111/jpy.12163
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of diversity of chromophytic phytoplankton in a mangrove ecosystem using rbcL gene sequencing

Abstract: Phytoplankton forms the basis of primary production in mangrove environments. The phylogeny and diversity based on the amplification and sequencing of rbcL, the large subunit encoding the key enzyme ribulose-1, 5-bisphosphate carboxylase/oxygenase was investigated for improved understanding of the community structure and temporal trends of chromophytic eukaryotic phytoplankton assemblages in Sundarbans, the world's largest continuous mangrove. Diatoms (Bacillariophyceae) were by far the most frequently detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Sagar Island is the biggest island of Indian Sundarbans and marks the westernmost part of this ecoregion. A predesignated station named as Stn3 (Mooriganga) (21° 40ʹ 40.6ʺ N, 88° 09ʹ 19.2ʺ E) which is part of the Sundarbans Biological Observatory Time Series (SBOTS) monitored since 2010 has been considered in this study (Bhattacharjee, Samanta, Danda, & Bhadury, ; Choudhury, Das, Philip, & Bhadury, ; Samanta & Bhadury, ). Huge freshwater from the Mooriganga estuary and diurnal tidal influx of coastal water from the Bay of Bengal gives rise to typical estuarine conditions in this station.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sagar Island is the biggest island of Indian Sundarbans and marks the westernmost part of this ecoregion. A predesignated station named as Stn3 (Mooriganga) (21° 40ʹ 40.6ʺ N, 88° 09ʹ 19.2ʺ E) which is part of the Sundarbans Biological Observatory Time Series (SBOTS) monitored since 2010 has been considered in this study (Bhattacharjee, Samanta, Danda, & Bhadury, ; Choudhury, Das, Philip, & Bhadury, ; Samanta & Bhadury, ). Huge freshwater from the Mooriganga estuary and diurnal tidal influx of coastal water from the Bay of Bengal gives rise to typical estuarine conditions in this station.…”
Section: Methodsmentioning
confidence: 99%
“…Four stations located across four estuaries in Sundarbans selected for this study are shown in Figure 1. Sagar Island is the biggest island of Indian Sundarbans and marks the westernmost part of this has been considered in this study (Bhattacharjee, Samanta, Danda, & Bhadury, 2013;Choudhury, Das, Philip, & Bhadury, 2015;Samanta & Bhadury, 2014). Huge freshwater from the Mooriganga estuary and diurnal tidal influx of coastal water from the Bay of Bengal gives rise to typical estuarine conditions in this station.…”
Section: Sampling Stations Of Estuaries In Sundarbansmentioning
confidence: 99%
See 1 more Smart Citation
“…Bloom forming centric diatom genera such as Thalassiosira Cleve and Coscinodiscus Ehrenberg are detectable throughout the year in Sundarbans highlighting their importance in aquatic primary production (Biswas et al . ; Samanta & Bhadury ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, very limited information exists to date from the context of Thalassiosira ecology in mangrove ecosystems. Based on a recent study using form ID large subunit of RuBisCO ( rbc L) phylogeny it has been shown that diatom assemblages are overwhelmingly dominated by Thalassiosira throughout the year in Sundarbans (Samanta & Bhadury ). Thus it is important to establish cultures of Thalassiosira from mangrove environments such as Indian Sundarbans for better understanding of their ecological significance in this ecosystem.…”
Section: Introductionmentioning
confidence: 99%